Pengaruh Pengetahuan Awal Akuntansi, Kecerdasan Emosional Dan Efikasi Diri Terhadap Tingkat Pemahaman Akuntansi - Ainun Jariyah; Rochmawati Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
This study was conducted to examine and analyze the effect of prior knowledge of accounting, emotional intelligence and self-efficacy on the level of understanding of accounting in accounting education students, Faculty of Economics, State University of Surabaya. This research is a type of quantitative method. The research sample used is a saturated sampling technique with a total of 96 PAK undergraduate students departing 2017. Questionnaires (questionnaires) and documentation are techniques in collecting data. The results showed that initial accounting knowledge had a partial effect, emotional intelligence had no partial effect and self-efficacy had no partial effect. The results of the F test show that there is a simultaneous influence of initial accounting knowledge, emotional intelligence and self-efficacy on the level of accounting understanding in accounting education students, Faculty of Economics, Universitas Negeri Surabaya.